2004
DOI: 10.1091/mbc.e04-06-0443
|View full text |Cite
|
Sign up to set email alerts
|

The Fission Yeast Kinetochore Component Spc7 Associates with the EB1 Family Member Mal3 and Is Required for Kinetochore–Spindle Association

Abstract: A critical aspect of mitosis is the interaction of the kinetochore with spindle microtubules. Fission yeast Mal3 is a member of the EB1 family of microtubule plus-end binding proteins, which have been implicated in this process. However, the Mal3 interaction partner at the kinetochore had not been identified. Here, we show that the mal3 mutant phenotype can be suppressed by the presence of extra Spc7, an essential kinetochore protein associated with the central centromere region. Mal3 and Spc7 interact physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 72 publications
3
65
0
Order By: Relevance
“…Recent work in fission yeast demonstrated that the KNL-1 homologue Spc7 is not required for Ndc80 localization, but also reported synthetic lethal genetic interactions between spc7 and mis6 (CENP-I) or sim4 (CENP-K) mutants (Kerres et al, 2004), consistent with the synergistic defects we describe here for hKNL1/ CENP-K double inhibitions. Overall, these results suggest evolutionary plasticity in kinetochore assembly, specifically in the recruitment of the critical Ndc80 complex.…”
Section: M Cheeseman Et Alsupporting
confidence: 88%
See 1 more Smart Citation
“…Recent work in fission yeast demonstrated that the KNL-1 homologue Spc7 is not required for Ndc80 localization, but also reported synthetic lethal genetic interactions between spc7 and mis6 (CENP-I) or sim4 (CENP-K) mutants (Kerres et al, 2004), consistent with the synergistic defects we describe here for hKNL1/ CENP-K double inhibitions. Overall, these results suggest evolutionary plasticity in kinetochore assembly, specifically in the recruitment of the critical Ndc80 complex.…”
Section: M Cheeseman Et Alsupporting
confidence: 88%
“…A key player in kinetochore assembly in C. elegans is KNL-1, which functions downstream of the inner kinetochore components such as CENP-A, but upstream of all known outer kinetochore proteins (Desai et al, 2003;Cheeseman et al, 2004). KNL-1 belongs to a conserved protein family that includes budding yeast Spc105 (Nekrasov et al, 2003), fission yeast Spc7 (Kerres et al, 2004), Drosophila Spc105R (Przewloka et al, 2007), and a novel protein previously identified in human cells known as AF15q14, D40, CASC5, or Blinkin (Cheeseman et al, 2004;Obuse et al, 2004;Kiyomitsu et al, 2007). AF15q14 is present in all vertebrates including chicken (Gallus gallus).…”
Section: Introductionmentioning
confidence: 99%
“…S. pombe strains were grown in rich Protein analysis. Protein extracts were prepared as described previously (35). Blots were probed with anti-green fluorescent protein (anti-GFP) antibody (polyclonal rabbit; Invitrogen) followed by alkaline phosphatase (AP)-conjugated secondary antibody (affinity-purified goat anti-rabbit IgG [Fc]; Promega, Madison, WI) and detected with 5-bromo-4-chloro-3-indolylphosphate/nitroblue tetrazolium (BCIP/NBT) as the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work in fission yeast indicates that Mal3 interacts with the kinetochore component Spc7 (homologue of budding yeast Spc105 and human KIAA1570) during mitosis and is important for accurate chromosome segregation (Kerres et al, 2004). We have recently shown that in the absence of Mal3, mitotic delay is induced, in which the Bub1 branch of the spindle checkpoint is activated, and Bub1-localizing kinetochores are associated for a prolonged period of time with only one of two separating spindle pole bodies (SPBs) Asakawa and Toda, 2006).…”
Section: Introductionmentioning
confidence: 99%